FROM LIFESTYLE INTERVENTIONS TO BARIATRIC SURGERY: AN OVERVIEW OF OBESITY TREATMENT MODALITIES - Krzysztof Jamroch; Aleksandra Marek; Katarzyna Garncarz; Karolina Dziki; Wiktoria Dybizbańska; Zofia Nowakowska; Agnieszka Burzej; Mateusz Kacalak; Maciej Komenda; Julia Szklarska-Komenda (International Journal of Innovative Technologies in Social Science, 2025)
Obesity is a chronic, multifactorial disease associated with serious metabolic, cardiovascular, psychological, and socioeconomic consequences. This review aims to synthesize current evidence on the contemporary treatment strategies for obesity: lifestyle interventions, pharmacotherapy, endoscopic therapies, and bariatric surgery. Our findings indicate, that obesity develops through the interaction of genetic, metabolic, behavioral, and environmental factors, making simple lifestyle-based approaches insufficient for many patients. While multi-component lifestyle interventions remain the foundation of therapy, their long-term effectiveness is limited. The effectiveness strongly depends on patient’s involvement, usually fluctuating between 2.4% and 10.8% of reduced total body weight per year. Modern drugs are the second stage of treatment. According to our results, the most effective is tirzepatide - dual incretin agonist - that demonstrates weight loss outcomes averaging up to 25.3% in 88 weeks follow-up. The next step of managing obesity is endoscopic treatment, that provide profound efficacy with favorable safety profiles. For example, endoscopically inserted intragastric balloons can lead to an average weight loss of around 25% within 12 months. Endoscopic methods seem to be a promising alternative for patients who are unwilling or unsuitable for surgical interventions. The most effective and durable treatment from many years remains bariatric surgery, offering substantial weight reduction and improvement in comorbidities. The most commonly performed is laparoscopic sleeve gastrectomy, averaging 35.14% total body weight loss after one year. However, we should remember that bariatric surgery also carries the highest risk of serious complications and it is the most invasive of all available obesity treatment methods.